Bank Supervision and Corporate Finance - Beck, Thorsten; Demirguc-Kunt, Asli; Levine, Ross (World Bank, Washington, DC, 2014)
The authors examine the impact of bank supervision on the financing obstacles faced by almost 5,000 corporations across 49 countries. They find that firms in countries with strong official supervisory agencies that directly monitor banks tend to face greater financing obstacles. Moreover, powerful official supervision tends to increase firm reliance on special connections and corruption in raising external finance, which is consistent with political and regulatory capture theories. Creating a supervisory agency that is independent of the government and banks mitigates the adverse consequences of powerful supervision. Finally, the authors find that bank supervisory agencies that force accurate information disclosure by banks and enhance private monitoring tend to ease the financing obstacles faced by firms.